Strategizing the Development of Food Markets in the Region by Employing Supply Chain Management: A Product-Territorial and Product-Spatial Approach - Natalia Leonidovna Kuzmina; Lyubov Leonidovna Tonysheva; Darya Vladimirovna Chumlyakova (International Journal of Supply Chain Management, 2019)
This article substantiates the need to strategize food markets’ development in the region as components of the region's reproduction cycle of food products by using supply chain management. The authors suggest two approaches in terms of this development in the region. Within the framework of the product-territorial approach, strategies have been defined for the development of markets for individual food products in order to activate internal sources of forming product supply. Within the framework of the product-spatial approach, the need to develop strategic priorities for the development of local food markets to best meet the population's food needs, taking into account inter-municipal socio-economic differentiation, has been justified. The scheme for the strategic supply chain management implementation of the local food markets’ development is based on embedding strategic objectives, priorities, and guidelines for their development in the strategies of the socio-economic development in the region and its municipal formations.